Associations of long-term exposure to ambient fine particulate matter and nitrogen dioxide with lung function: A cross-sectional study in China. (November 2020) - Hou, Dongni; Ge, Yihui; Chen, Cuicui; Tan, Qiang; Chen, Renjie; Yang, Yanjie; Li, Li; Wang, Jian; Ye, Maosong; Li, Chun; Meng, Xia; Kan, Haidong; et al.
Highlights: Effects of long-term exposure to air pollution on lung function remains unclear. We conducted a cross-sectional, multicenter study with 5281 adults from Shanghai, China. Exposure to ambient PM2.5 and NO2 were negatively associated with lung function decline. For PM2.5, stronger negative associations were found in the obese and ever-smokers. For NO2, stronger negative associations were found in the obese, never-smokers and females. Abstract: Background: Few studies have evaluated the effects of ambient air pollution exposure on lung function, especially in areas with high air pollution levels. Objectives: To investigate the associations of annual concentrations of particulate matter with diameters < 2.5 μm (PM2.5 ) and nitrogen dioxide (NO2 ) with adult lung function in Shanghai, China. Methods: We included 5276 permanent residents aged ≥ 20 years. Annual residential exposure to PM2.5 and NO2 was estimated by validated satellite-based and land use regression models, respectively. The effects of PM2.5 and NO2 on lung function were estimated separately using multivariable linear regression, adjusting for potential confounders. Results: Higher exposure to PM2.5 and NO2 was significantly associated with lower forced vital capacity (FVC), inspiration capacity (IC), and vital capacity (VC). An increase of 10 μg/m 3 in the annual average PM2.5 exposure was associated with a 45.83 ml (95% CI: −82.59, −9.07) lower FVC, 1.36 (95% CI: −2.42, −0.29) lower FVC of % predicted (FVC%pred ), 121.98 ml (95% CI: −164.38, −79.57) lower IC, and 89.12 ml (95% CI −124.94, −53.3) lower VC. For NO2, an increase of 10 μg/m 3 in the annual average concentration was associated with 26.65 ml (95% CI: −46.29, −7.00) lower FVC, 0.70 (95% CI: −1.27, 0.13) lower FVC%pred, 65.26 ml (95% CI: −87.76, −42.76) lower IC, and 45.88 ml (95% CI: −65.03, −26.73) lower VC. The estimated effects on FEV1 were −10.25 ml (95% CI: −40.92, 20.42) and −0.29% (95% CI: −1.40, 0.82) per 10 μg/m 3 increase in PM2.5 and −0.74 ml (95% CI: −17.13, 15.65) and 0.01% (95% CI: −0.58, 0.61) per 10 μg/m 3 increase in NO2, which were not statistically significant. Stratified analysis showed that the estimated effects of PM2.5 were greater in the healthy subgroup than the COPD patients. Obese individuals were more susceptible to adverse effects of PM2.5 and NO2 on lung function. Education level showed no or only weak evidence of modification of the associations between air pollution and lung function. Conclusion: In this study, long-term exposure to ambient air pollutants was significantly associated with impaired lung function, presenting as restrictive ventilatory patterns.